BRIDGING DIVIDES: HOPE, INCLUSION, AND LEGITIMACY IN THE TRUMP-MAMDANI ENCOUNTER (Contemporary Journal of Social Science Review, 2025)
This study employs van Dijk’s socio-cognitive approach to examine how linguistic choices in the press interaction between President Donald Trump and NYC Mayor-elect Zohran Mamdani construct political legitimacy, inclusion, and power relations. There is a lack of understanding regarding how mental models and shared ideologies specifically shape the discursive construction of hope and the normalization of minority leadership through counter-hegemonic narratives within institutional settings.This study presents a refined Critical Discourse Analysis (CDA) of the post-meeting press interaction between U.S. President Donald Trump and New York City Mayor-elect Zohran Mamdani, emphasizing Teun A. van Dijk's socio-cognitive approach. The paper explores the means by which linguistic choices construct political legitimacy, inclusion, hope, and power relations in an institutional context. The analysis draws exclusively from the verified transcript of the press interaction, focusing on lexical selection, pronoun usage, evaluative language, thematic emphasis, modality, and ideological strategies. Findings indicate that Trump’s discourse enacts institutional authority via positive self-presentation, evaluative endorsement, and conditional modality, reinforcing dominant ideologies of hierarchical power. In contrast, Mamdani’s discourse promotes collective identity, affordability, and civic belonging through inclusive language and mitigation strategies, functioning as a counter-hegemonic yet aligned narrative that normalizes minority leadership without overt identity marking. By applying van Dijk’s socio-cognitive perspective, this refinement highlights the role of mental models and shared ideologies shape discourse production and interpretation, contributing to CDA scholarship on political discourse, democratic legitimacy, and the discursive construction of hope in contemporary U.S. governance.